(3QSGdI (B( (3fKQ hTYQ(B)s - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s
(3ChdgG (B:s
(3GeG HYO , aCgOi JSdjeG UGZ GdhLO bQWg hfXeJ HfGf GdNdhU SeWg hMGc GdZQGe GdYPQi eQWg hKfGA fTQJ ai CafjI GdfLGHg eWGQag s
(3BNQgG (B:s
(3dG JDGNPg dMhH UOg hNWhH ChgfJ efg GdYXGeG hdc GdaVd Ydjg eGSQi efc QTO jHgQ GdeSc NJGeG s
(3GdfSNI HgG MhGTs
(3cJHgG Edi NGdO GdcQOi GdfbTHfOi hgh ai HZOGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B367s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs